The analysis and optimization of thermal sensation of train drivers under occupational thermal exposure - Yang, Zeyun; Zhou, Wenjun; Xu, Gang; Li, Xinkang; Yang, Mingzhi; Xiao, Qiang; Fan, Chaojie; Peng, Yong (Frontiers in Public Health, 2023)
Prolonged exposure of train drivers to thermal discomfort can trigger occupational safety and health (OSH) risks and cause physical and mental injuries. The traditional method of simply treating human skin as a wall surface is unable to observe accurate skin temperature changes or to obtain human thermal comfort that varies in response to the thermal environment. Therefore, in order to investigate and optimize the thermal comfort of train drivers, the stolwijk human thermal regulation model has been adopted in this paper. In order to reduce the time consuming design optimization, a pointer optimization algorithm based on radial basis function (RBF) approximation was used for optimal design of the train cab ventilation system with the aim of better drivers' thermal comfort. A train driver thermal comfort model was developed using star-ccm+ and 60 operating conditions were sampled using an Optimal Latin Hypercube Design (Opt LHD). We analyzed the effects of air supply temperature, air supply volume, air supply angle, solar radiation intensity and solar altitude angle on the local thermal susceptibility ticket (LTSV) and overall thermal susceptibility ticket (OTSV) of the train driver. Finally, the optimal air supply parameters for HVAC in the train cabin under extreme summer conditions were obtained, which effectively improved the thermal comfort of the driver.